(untitled) (Mugda Medical College Journal, 2022)
Background: World has changed tremendously with COVID -19. Every aspect of human life is affected by COVID-19. Pregnant mothers and their newborns are also at risk of COVID-19. Objective: The objectives of this study were to review and discuss on various important issues regarding essential and immediate newborn care & resuscitation of newborn during delivery in the perspective of COVID-19, timing of testing of newborn for Covid-19, if newborn is positive of Covid-19 what measures should be taken and breast feeding the newborn of Covid-19 positive mother etc. Methods: The study is designed on the basis of secondary information from different recent studies and guideline. For this, the internet has been used as source of information. Results: Results of different recent studies and WHO & national guidelines are that the routine care of newborn is not different from national guideline, additional measures for infection prevention and control should be taken by both health service provider and caregiver or mother. Newborn should be tested for COVID-19 routinely if mother is suspected or confirmed Covid-19 positive. If testing is not available suspected newborn should be managed as Covid-19 positive case. Till date Covid -19 virus is not detected in breast milk or transmitted through breast milk. So, multiple benefits of breast feeding substantially outweigh the potential risks of transmission and illness associated with COVID-19. In the community transmission phase, all newborns coming to SCANU should be considered as COVID-19 suspected neonate and should assess before admission to SCANU. Mother or caregiver should be counseled about post-natal follow up and also for danger signs. Conclusion: As we are in the intermediate stage of corona virus outbreak the available information be changed according to further studies. The main attempt of this study is to summarize the literature about update care of newborn during COVID-19 pandemic. Mugda Med Coll J. 2022; 5(1): 34-40